Roar of the thunder dragon - West, Tracey, 1965-; Jones, Damien (New York, NY : Branches/Scholastic Inc., 2017)
Lalo the baby lightning dragon has been taken by Eko, a rogue Dragon Master, who ran away with her thunder dragon years before--now she is back looking to make allies of the other dragon masters, and so gain control over all of the dragons in Griffith.
Appeals to 1st-3rd graders.
Reading level grade 2.
Keywords: Dragons -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Wizards -- Fiction; Magic -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction; Action and adventure fiction